High Dose Vardenafil Blunts the Hypertensive Effects of Toll-Like Receptor 3 Activation During Pregnancy - Balasubbramanian, Dakshnapriya; Dharani, Sathish; Tauseef, Mohammad; Khan, Mansoor A.; Rahman, Ziyaur; Mitchell, Brett M. (Frontiers in Virology, 2021)
The maternal innate immune system plays a central role in preeclampsia (PE). Toll-like receptors (TLRs) are innate immune system receptors that recognize characteristics of extracellular endogenous ligands or pathogens, and their activation leads to a pro-inflammatory immune response. We and others have reported that excessive activation of TLRs causes pregnancy-dependent hypertension in animals and is associated with PE in women. Activation of TLR3 by poly I:C mimics the innate immune system activation by viruses that women who develop PE encounter during pregnancy. Vardenafil was approved by the FDA for erectile dysfunction but has recently been examined as a potential PE medication due to studies done with a similar drug, sildenafil. Preclinical as well as recent clinical studies demonstrate the potential effectiveness of sildenafil for PE. However, vardenafil is more potent than sildenafil and acts by increasing expression of placental growth factor in addition to increasing cGMP levels. We hypothesized that vardenafil will be more potent and effective in reducing the negative health effects in a mouse model of virus-induced PE. Pregnant mice were injected with the TLR3 agonist poly I:C (PPIC) on gestational days 13, 15, and 17. We treated PPIC mice with a high dose of vardenafil (50 mg human equivalent), a lower dose of vardenafil (20 mg human equivalent), or sildenafil (50 mg human equivalent) on gestational days 15-17 after hypertension was established. Daily i.p. injections of either high dose or low dose vardenafil significantly decreased systolic blood pressure in PPIC mice whereas sildenafil had no effect. There were no differences in body weight between the groups. The splenomegaly induced in PPIC mice was ameliorated in high dose vardenafil-treated PPIC mice, while low dose vardenafil-treated and sildenafil-treated PPIC mice still exhibited splenomegaly. High dose vardenafil-treated PPIC mice also did not exhibit any fetal demise characteristic of PPIC mice, while low dose vardenafil-treated and sildenafil-treated PPIC mice still had significantly increased incidences of fetal demise. These data support the notion that high dose vardenafil may be safe and effective at reducing blood pressure during a virus-associated hypertensive pregnancy.